Pictorial essay: Pneumocephalus - Cihangiroglu, Mutlu; Unal, Birsen; Ozdemir, Hüseyin; Yildirim, Hanifi; Ogur, Erkin (My University, 2003)
Imaging in pneumocephalus aids in the diagnosis and management of this condition, which usually results from trauma, iatrogenic causes, infections, tumors, and cranium abnormalities. The role of computed tomography and magnetic resonance imaging is especially addressed in this article.
Pnömosefali.
Keywords: Humans; Magnetic Resonance Imaging; Pneumocephalus; Tomography, X-Ray Computed; computer assisted tomography; human; nuclear magnetic resonance imaging; pathology; pneumocephalus; radiography; review